Advances in Research on the Involvement of Selenium in Regulating Plant Ecosystems - Wei Chao; Shen Rao; Qiangwen Chen; Weiwei Zhang; Yongling Liao; Jiabao Ye; Shuiyuan Cheng; Xiaoyan Yang; Feng Xu (Plants, 2022)
Selenium is an essential trace element which plays an important role in human immune regulation and disease prevention. Plants absorb inorganic selenium (selenite or selenate) from the soil and convert it into various organic selenides (such as seleno amino acids, selenoproteins, and volatile selenides) via the sulfur metabolic pathway. These organic selenides are important sources of dietary selenium supplementation for humans. Organoselenides can promote plant growth, improve nutritional quality, and play an important regulatory function in plant ecosystems. The release of selenium-containing compounds into the soil by Se hyperaccumulators can promote the growth of Se accumulators but inhibit the growth and distribution of non-Se accumulators. Volatile selenides with specific odors have a deterrent effect on herbivores, reducing their feeding on plants. Soil microorganisms can effectively promote the uptake and transformation of selenium in plants, and organic selenides in plants can improve the tolerance of plants to pathogenic bacteria. Although selenium is not an essential trace element for plants, the right amount of selenium has important physiological and ecological benefits for them. This review summarizes recent research related to the functions of selenium in plant ecosystems to provide a deeper understanding of the significance of this element in plant physiology and ecosystems and to serve as a theoretical basis and technical support for the full exploitation and rational application of the ecological functions of selenium-accumulating plants.